1997
DOI: 10.1128/mcb.17.7.3915
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Glutamate Dehydrogenase from Leishmania tarentolae Is a Guide RNA-Binding Protein

Abstract: To identify specific proteins interacting with guide RNAs (gRNAs) in mitochondrial ribonucleoprotein complexes from Leishmania tarentolae, fractionated and unfractionated mitochondrial extracts were subjected to UV cross-linking with added labeled gRNA and also with [␣-32 P]UTP-labeled endogenous RNA. An abundant 110-kDa protein (p110) localized in the T-V complex, which sediments in glycerol gradients at the leading edge of the 10S terminal uridylyltransferase peak, was found to interact with both types of la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 58 publications
0
24
0
Order By: Relevance
“…Interaction of yeast Eno1/2p with single-stranded DNA was reported previously (al-Giery and Brewer 1992). Numerous other proteins, including glycolytic enzymes, were already found to have RNA-or tRNA-binding capacities (Singh and Green 1993;Hentze 1994;Bringaud et al 1997;Pioli et al 2002). In the majority of cases, there was no direct evidence of the functional importance of these RNA-binding capacities of well known enzymes, but additional roles in RNA turnover and compartmentalization were suggested.…”
Section: Enolase Another Protein With Multiple Functionsmentioning
confidence: 88%
“…Interaction of yeast Eno1/2p with single-stranded DNA was reported previously (al-Giery and Brewer 1992). Numerous other proteins, including glycolytic enzymes, were already found to have RNA-or tRNA-binding capacities (Singh and Green 1993;Hentze 1994;Bringaud et al 1997;Pioli et al 2002). In the majority of cases, there was no direct evidence of the functional importance of these RNA-binding capacities of well known enzymes, but additional roles in RNA turnover and compartmentalization were suggested.…”
Section: Enolase Another Protein With Multiple Functionsmentioning
confidence: 88%
“…IP from mitochondrial extract was performed using Sepharose G beads coated with affinity-purified mouse polyclonal antibodies against recombinant Ltp26, recombinant Ltp28, and L. tarentolae 3Ј TUTase (Ltp26-IP, Ltp28-IP, and TUT-IP lanes). Immunodetection was performed with rabbit antibodies raised against purified Ltp26/Ltp28 complex, recombinant glutamate dehydrogenase (GDH) (Bringaud et al 1997), and TUTase. Ext, mitochondrial extract; Pre, proteins bound to G-beads coated with preimmune serum; Ab, proteins bound to G-beads coated with specific antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has had varied success. For example, in L. tarentolae, three proteins, p18, p51, and p110, were identified by RNA binding and then discovered to be the mitochondrial metabolic enzymes ATPase subunit b, aldehyde dehydrogenase, and glutamate dehydrogenase, respectively (Bringaud et al 1995(Bringaud et al , 1997, and a double knockout of the glutamate dehydrogenase gene had no effect on editing (Estévez et al 1999). TBRGG1, a mitochondrial protein from T. brucei that binds poly [U] and gRNAs, was cloned by homology to nucleolin and shown to cosediment with in vitro editing activity, but no role in editing has been ascribed to this protein (Leegwater et al 1995;Vanhamme et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Actually, other roles of GDHs have been reported. For instance, a membrane-bound form of GDH possesses a microtubule-binding activity (Rajas et al, 1996), and GDH reacts as an RNA-binding protein and shows a possible role in the regulation of transcription (Preiss et al, 1993;McDaniel, 1995;Bringaud et al, 1997). Recently, Cavallaro et al (1997) have identified GDH as one of the late memory-related genes in the hippocampus, and Frattini et al (1997) have identified GDH as a new member of the ring finger gene family in It would appear that we have just begun to unravel the mystery of GDHs and their role in a biological system.…”
Section: Discussionmentioning
confidence: 99%